Strategic Formulation Analysis of Business Development of PT Mega Power Surya (A Subsidiary of PT Mega Power Teknindo) - Gagah Daruhadi; Elly Yuliati; Fitri Mutiara Elgasari; Rhian Indradewa; Dimas Angga Negoro (PT. Publikasiku Academic Solution, 2023)
PT Mega Power Surya (MPS) is a subsidiary of PT Mega Power Teknindo (MPT) which is engaged in Renewable Energy, especially the Procurement of Goods and Services for Surya Power Generation as a business diversification of the Company PT Mega Power Teknindo. The main purpose of establishing PT MPS is to take advantage of promising business opportunities in expanding PT MPT's business in the field of Renewable energy on the basis of the encouragement of the Presidential Regulation RUEN, Minister of Energy and Mineral Resources and Local Government (RUED) and RUPTL, sustainable energy factors, Go Green and responding to the increase in electricity rates from PLN so that consumers who use electricity will be interested in using surya power plants, namely using natural resources that never run out even though they are used continuously and it is hoped that the price of electricity for consumers will be cheaper using Surya energy compared to fully using electrical energy from PLN. Companies need to plan strategies and conduct business model analysis. The strategy method uses the Value Proposition Canvas, IFE, EFE, VRIO, CPM, SWOT, IE Matrix, QSPM, Porter's Generic Strategy, and Lean Model Business Canvas. The results of this analysis can help in identifying the appropriate business model. With the right strategy and business model, it will enable the newly created company to become a competitive and sustainable company. Using Value Proposition Canvas, EFE, IFE, VRIO, CPM, SWOT, IE, QSPM, Porter's Generic Strategy, and Lean Business Model Canvas. This analytical method helps in determining the right business strategy for PT. Mega Power Surya.